Comparative characterization of lipids and volatile compounds of Beijing Heiliu and Laiwu Chinese black pork as markers. (August 2021) - Li, Jing; Zhang, Jiaqi; Yang, Yuanyuan; Zhu, Jiawei; He, Weizhao; Zhao, Qingyu; Tang, Chaohua; Qin, Yuchang; Zhang, Junmin
Graphical abstract: Highlights: Intramuscular fat content in Beijing Heiliu and Laiwu black (BHLB) pork were higher. Classes and individual lipids differed in BHLB and Duroc×(Landrace × Yorkshire) pork. Triglyceride levels significantly increased in BHLB pork. Two kinds of pork were well distinguished based on 39 volatiles identified. The potential lipid and volatile markers for pork discrimination were identified. Abstract: Chinese black pork is preferred by consumers due to its unique organoleptic characteristics, which are closely related to lipids and volatiles. The primary aim of this study was to reveal key lipids and volatiles for the differentiation of Duroc × (Landrace × Yorkshire) (DLY), and Beijing Heiliu and Laiwu black (BHLB) pork. Here, lipid and volatile profiles were comprehensively characterized and compared using untargeted lipidomic and volatilomic analysis. The BHLB pork showed higher intramuscular fat content ( p  < 0.05). The content of total monounsaturated fatty acids, along with C16:1, C17:1, C18:1, and C20:1, was higher in BHLB pork compared with DLY pork ( p  < 0.05). Lipidomic analysis showed that DLY and BHLB pork significantly differed in lipids at the class and molecular levels. The BHLB pork had significantly more triglyceride and less lysophosphatidylcholine compared with DLY pork ( p  < 0.05). In positive and negative modes, 34 and 21 potential lipid markers, respectively, were selected for the discrimination of DLY and BHLB pork. In addition, volatilomic analysis showed that DLY and BHLB pork were well distinguished, and 13 volatiles were considered as potential discriminatory markers. Our findings provide a comprehensive lipidomic and volatilomic profiles characteristic of BHLB pork and will hopefully provide an important basis for the effective identification of Chinese black pork.